Patterns of calcium oxalate monohydrate crystallization in complex biological systems; IOP Conference Series: Materials Science and Engineering; Vol. 168 : Radiation-Thermal Effects and Processes in Inorganic Materials (RTEP2016) - Golovanova О. А. (Physical and chemical phenomena in inorganic materials in radiation, electrical and thermal fields, 2017)
Title screen